Students’ Mathematical Literacy in Solving PISA Problem Using Indonesian Cultural Context - Ratri Murdy Andari; Rini Setianingsih (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2021)
This study aims to examine students’ mathematical literacy in solving PISA problems using the Indonesian cultural context. This is a descriptive study with a qualitative approach. As the subject of this study are three 9th grade students with high, average, and low mathematical abilities. In collecting the data, the researchers used three instruments, namely, mathematical ability test, mathematical literacy test, and interview guidelines. The results reveal that student with high mathematical ability meets all indicators in the process of formulating, employing, and interpreting. Otherwise, students with average or low mathematical abilities only meet some indicators in the process of mathematical literacy. Therefore, it is suggested for the teacher to provide practice especially for students having average or low mathematical abilities with literacy problems using contexts that exist in students’ life, such as the Indonesian cultural context